What Wordsworth Planted - Lindstrom, Eric (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
This essay shows how the metaphor of “planting” assumes a cluster of meanings beyond horticulture in the romantic age. I pursue the associative dimensions of that figure as an index of both sexuality and obliquely imperial concerns in Wordsworth and his critics. The promiscuity of this word disrupts a received image of the poet as stodgy, self-directed, and somehow verbally and otherwise chaste. I reexamine frankly moving passages from the “memory fragment,” two-book Prelude and from the elegy “Peele Castle.” At the same time the essay heeds the injunction David Simpson offers in the title of his recent essay, “Wordsworth and Empire—Just Joking,” by pursuing the trace of Wordsworth’s possible jokes and the way they extend rather than nullify his resonance to world-formation. As with the “planted” snowdrops of the Prelude, planting in general as a linguistic maneuver displays limit areas over which Wordsworth presumes an ambivalent control, and may not acknowledge willful desires when indeed they are projected.